Physician Communication and Patient Understanding of Molecular Testing Terminology. (24th August 2021) - Blee, Shannon M.; Shah, Rachel Pocock; Pinheiro, Ana P.M.; Switchenko, Jeffrey; Dixon, Margie; Owonikoko, Taofeek K.; Hill, Charles E.; Szabo, Stephen M.; Pentz, Rebecca D.
Abstract : Background: The use of molecular testing in oncology is rapidly expanding. The aim of this study was to determine how oncologists describe molecular testing and whether patients understand the terminology being used. Materials and Methods: Sixty conversations between oncologists and patients about molecular testing were observed, and the used technical terms were noted by the researcher. Patients were interviewed post-conversation to assess their understanding of the noted technical terms. A patient understanding score was calculated for each participant. Comparisons of the terms were conducted using χ 2 tests, Fisher's exact tests, or ANOVA when appropriate. Results: Sixty-one unique technical terms were used by oncologists, to describe seven topics. "Mutation" was a challenging term for patients to understand with 48.8% (21/43 mentions) of participants correctly defining the term. "Genetic testing" and "Gene" were understood a little more than half the time (53.3%; 8/15 and 56.4%; 22/39 respectively). "DNA" was well understood (80%; 12/15). There was no correlation between the terms being defined by the oncologist in the conversation, and the likelihood of the patient providing a correct definition. White participants were significantly more likely to understand both "mutation" and "genetic testing" than non-White participants. Forty-two percent ( n  = 25) of participants had an understanding score below 50%, and a higher family income was significantly correlated with a higher score. Conclusion: Our results show that oncologists use variable terminology to describe molecular testing, which is often not understood. Because oncologists defining the terms did not correlate with understanding, it is imperative to develop new, improved methods to explain molecular testing. Implications for Practice: The use of molecular testing is expanding in oncology, yet little is known about how effectively clinicians are communicating information about molecular testing and whether patients understand the terminology used. The results of this study indicate that patients do not understand some of the terminology used by their clinicians and that clinicians tend to use highly variable terminology to describe molecular testing. These results highlight the need to develop and implement effective methods to explain molecular testing terminology to patients to ensure that patients have the tools to make autonomous and informed decisions about their treatment. Abstract : In the past decade, identifying genomic markers and corresponding targets through molecular testing has become increasingly important in the field of oncology, as it allows for a more personalized approach to cancer treatment. This article focuses on how oncologists describe molecular testing and whether patients understand the terminology being used.